751. Acute Respiratory Illness Hospitalizations Among Young Children: Multi-Center Viral Surveillance Network, United States, 2015–2016. (26th November 2018) - Rha, Brian; Campbell, Angela P; McDaniel, Darius; Selvarangan, Rangaraj; Halasa, Natasha; Englund, Janet; Boom, Julie A; Azimi, Parvin H; Weinberg, Geoffrey A; Staat, Mary A; Singer, Monica N; Sahni, Leila C; et al.
Abstract: Background: Viral infections are a significant cause of severe acute respiratory illnesses (ARI) in young children. Understanding the current epidemiology of these viruses is important for informing treatment and prevention measures. We describe the New Vaccine Surveillance Network (NVSN) and report preliminary results from 2015 to 2016. Methods: Prospective active surveillance for hospitalized ARI was conducted from November 1, 2015 to June 30, 2016 among children <5 years of age at seven pediatric hospital sites (figure) using a broad case definition based on admission diagnoses. Parent interviews and medical chart reviews were performed, and mid-turbinate nasal and throat flocked swabs and/or tracheal aspirates were tested for adenovirus, human metapneumovirus (HMPV), influenza, parainfluenza viruses (PIV) 1–3, respiratory syncytial virus (RSV), and rhinovirus/enterovirus using molecular diagnostic assays at each site. Asymptomatic controls <5 years of age were also enrolled. Results: Among 2, 974 hospitalized children with ARI whose specimens were tested for viruses, 2, 228 (75%) were <2 years old, with 745 (25%) 0–2 months, and 309 (10%) 3–5 months old. The majority were male (58%; n = 1, 732) and 63% ( n = 1, 093) had no documented comorbid conditions. The median length of stay was 2 days; 1, 683 (57%) received supplemental oxygen, 435 (15%) were admitted to intensive care, 95 (3%) required mechanical ventilation, and 1 (<1%) died. Viruses were detected in 2, 242 (75%) children with ARI, with >1 virus detected in 234 (8%). RSV was detected in 1, 039 (35%) children with ARI, HMPV in 245 (8%), influenza in 104 (4%), and PIV-1, PIV-2, and PIV-3 in 49 (2%), 2 (<1%), and 78 (3%), respectively. Rhinovirus/enterovirus was detected in 849 (29%) and adenovirus in 118 (4%) children with ARI, but were also detected in 18% ( n = 227) and 5% ( n = 60), respectively, of the 1, 243 controls tested; the other viruses were more rarely detected in controls. Conclusion: During the 2015–2016 season, viral detections were common in young children hospitalized for ARI at seven US sites. NVSN combines clinical data with current molecular laboratory techniques to describe respiratory virus epidemiology in cases of hospitalized pediatric ARI in order to inform current and future prevention, treatment, and healthcare utilization measures. Disclosures: N. Halasa, Sanofi Pasteur: Investigator, Research support. GSK: Consultant, Consulting fee. Moderna: Consultant, Consulting fee. J. Englund, Gilead: Consultant and Investigator, Consulting fee and Research support. Novavax: Investigator, Research support. GlaxoSmithKline: Investigator, Research support. Alios: Investigator, Research support. MedImmune: Investigator, Research support. J. V. Williams, Quidel: Board Member, Consulting fee. GlaxoSmithKline: Consultant, Consulting fee.